Global survey data on rice breeders' characteristics and willingness to adopt alternative breeding methods - Lenaerts, Bert; Collard, Bertrand C. Y.; de Mey, Yann; Demont, Matty (Elsevier, 2019)
The data presented in this article contains information on 189 rice breeders from 51 rice-growing countries around the world. Firstly, this unique dataset permits to lay down a baseline of currently used breeding methods. Secondly, the data allow to make an assessment of the adoption behavior of rice breeders towards alternative breeding methods, and in specific rapid generation advance. A global online survey in Google Forms was conducted to obtain information about different aspect of the adoption process. Both the raw and cleaned data are made available, along with Stata code to promote further research into adoption of breeding methods by public and private breeding institutes.